Analisis Penjualan Produk Olahan Pisang dan Ubi pada Usaha Dream Food sebagai Makanan Kekinian - Naibaho, Annisa Azzahra; Lase, Tri Wandani; Adeline, Adeline; Harefa, Meilinda Suriani (Edutech Journals, 2024)
Bananas and sweet potatoes are foods that are easy to get and are popular with many people in Indonesia, especially the younger generation, and considering the health benefits of bananas and sweet potatoes, a campaign has been launched to encourage the younger generation to be more active in consuming bananas and sweet potatoes. sweet potato. The main objective of this article is to understand the sales of processed banana and sweet potato products in the Dream Food business as contemporary food products. The research method used in this research includes literature study methodology, namely using qualitative methods to obtain descriptive data. The results of this research are that marketing processed bananas and cassava can provide promising and profitable opportunities for future businesses